Hubungan Pengetahuan Ibu, Nyeri Punggung dan Kualitas Tidur dengan Pelaksanaan Senam Hamil Trim III di PMB “M” Ciherang Kab. Cianjur Tahun 2023 - Nurulita, Alika; Astarie, Aida Diana; Santi, Agus (Indonesian Journal Publisher, 2023)
Trim III pregnancy exercise is a type of physical exercise that involves carrying out several special movements intended to improve the health of pregnant women and build and prepare the muscles needed to undergo childbirth well. This research aims to identify the relationship between. maternal knowledge, back pain, and sleep quality with the implementation of Trim III Pregnancy Exercises at PMB. M Ciherang, Cianjur Regency in 2023. This research uses analytical descriptive research using quantitative methods, namely a cross-sectional approach. The sample collection technique used in this research used a nonprobability sampling technique with purposive sampling. The number of samples in this study were all third trimester pregnant women, totaling 30 respondents who participated in the implementation of pregnancy exercise at PMB.M Ciherang, Cianjur district in 2023. The results of the Chi-Square test in this study showed that there was a significant relationship between knowledge and carrying out pregnancy exercises, obtained a P.Value of 0.048 (< 0.05), back pain with carrying out pregnancy exercises, obtained a P.Value of 0.008 (< 0.05), quality of sleep with carrying out pregnancy exercises, obtained a P value .Value.of 0.028 (< 0.05).